1992
DOI: 10.1002/mds.870070309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a selective partil D1 agonist, CY 208‐243, in de novo patients with Parkinson disease

Abstract: A selective dopamine D1-receptor agonist, CY 208-243, was administered to 23 de novo patients who had had Parkinson disease (PD) for less than or equal to 3 months. The drug was first used as monotherapy and then in some patients in combination with a dopamine D2-receptor agonist, bromocriptine. Results showed that CY 208-243 exerted a mild antiparkinsonian action, and tremor was the main symptom that consistently improved. The addition of bromocriptine less than or equal to 15 mg to CY 208-243 did not result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Thus, de novo treatment with the D 1 agonist SKF-81,297 led to the development of AIMs in the 6-OHDA-lesioned rat (Dupre et al, 2007;Jaunarajs et al, 2009), and de novo administration of the D 1 agonist SFK-82,958 led to the development of dyskinesia in the MPTP-lesioned macaque (Blanchet et al, 1996b;Goulet et al, 1996). To our knowledge, only one de novo study with a selective D 1 agonist was performed in PD patients; in that study, no dyskinesia was reported after treatment with the D 1 partial agonist CY-208,243 (Emre et al, 1992). D 2 receptors also appear to be involved in dyskinesia, although they are traditionally regarded as being less involved than D 1 receptors, perhaps because of the de novo studies with dopamine agonists and of the postmortem data discussed above.…”
Section: Dopamine Receptorsmentioning
confidence: 95%
“…Thus, de novo treatment with the D 1 agonist SKF-81,297 led to the development of AIMs in the 6-OHDA-lesioned rat (Dupre et al, 2007;Jaunarajs et al, 2009), and de novo administration of the D 1 agonist SFK-82,958 led to the development of dyskinesia in the MPTP-lesioned macaque (Blanchet et al, 1996b;Goulet et al, 1996). To our knowledge, only one de novo study with a selective D 1 agonist was performed in PD patients; in that study, no dyskinesia was reported after treatment with the D 1 partial agonist CY-208,243 (Emre et al, 1992). D 2 receptors also appear to be involved in dyskinesia, although they are traditionally regarded as being less involved than D 1 receptors, perhaps because of the de novo studies with dopamine agonists and of the postmortem data discussed above.…”
Section: Dopamine Receptorsmentioning
confidence: 95%
“…Several compounds, with high binding affinity and selectivity for the D 1 receptor had even entered clinical trials as anti-parkinsonian or anti-psychotic drugs, but were discontinued later or no development information reported for several years. [134][135][136][137] These ligands include conformationally flexible benzazepines, for example, SKF-83566 (2) In addition to their low intrinsic partial agonist activity, the failure of these compounds was largely due to poor oral bioavailability and rapid tolerance.…”
Section: D I S C O V E R Y O F N E W D 1 R E C E P T O R ( P I -D 1mentioning
confidence: 99%
“…Recent evidence indicates that tacrine-induced jaw movements are reduced by SKF 82958 but not by SKF 38393 ), a pattern which is similar to the effects of these agents in MPTP parkinsonism. Interest in D 1 agonists as potential antitremorogenic agents is warranted, in view of a clinical report indicating that the D 1 agonist CY 208-243 suppressed parkinsonian tremor; according to Emre et al (1992), CY 208-243 exerted a mild antiparkinsonian effect, but "tremor was the main symptom that consistently improved" (p. 239).…”
Section: Introductionmentioning
confidence: 95%